Neurological Complications of Solid Organ Transplantation. (July 2013) - Pruitt, Amy A.; Graus, Francesc; Rosenfeld, Myrna R.
Solid organ transplantation (SOT) is the preferred treatment for an expanding range of conditions whose successful therapy has produced a growing population of chronically immunosuppressed patients with potential neurological problems. While the spectrum of neurological complications varies with the type of organ transplanted, the indication for the procedure, and the intensity of long-term required immunosuppression, major neurological complications occur with all SOT types. The second part of this 2-part article on transplantation neurology reviews central and peripheral nervous system problems associated with SOT with clinical and neuroimaging examples from the authors' institutional experience. Particular emphasis is given to conditions acquired from the donated organ or tissue, problems specific to types of organs transplanted and drug therapy-related complications likely to be encountered by hospitalists. Neurologically important syndromes such as immune reconstitution inflammatory syndrome (IRIS), posterior reversible encephalopathy syndrome (PRES), and posttransplantation lymphoproliferative disorder (PTLD) are readdressed in the context of SOT.